Dóra Czeferner, Kultúrmisszió vagy propaganda? Feminista lapok és olvasóik Bécsben és Budapesten, Bölcsészettudományi Kutatóközpont Történettudományi Intézet, Budapest 2021, pp. 286 - Piotrowiak-Junkiert, Kinga (Porównania, 2025)
The article is a review of Dóra Czeferner’s 2021 book Kultúrmisszió vagy propaganda? Feminista lapok és olvasóik Bécsben és Budapesten (Mission or Propaganda? Women’s Magazines and their Readers in Vienna and Budapest). The monograph by the Hungarian researcher focuses on a quantitative and qualitative analysis of statistical data. The researcher examines the three most influential women’s magazines between 1907 and 1918 and discusses the topics they covered. Thanks to the great commitment of the most important activists of the women’s movement in the Austro-Hungarian Monarchy, namely Auguste Fickert, Vilma Glücklich and Rózsa Schwimmer, advanced pro-women education was introduced, especially in the matter of suffrage. The magazines “A Nő és a Társadalom” (Woman and Society), “A Nő. Feminista Folyóirat” (Woman. Feminist Magazine) and “Neues Frauenleben” (New Women’s Lives) also presented profiles of the most important feminist activists, the achievements of women abroad and the need to strengthen the role of women in society. Dóra Czeferner’s work is one of the most important research achievements concerning the situation of women, especially the history of women’s press at the beginning of the 20th century in our region.